2014
DOI: 10.4149/neo_2014_091
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 as a potential biomarker for carcinoma of oral cavity: a study in eastern India

Abstract: Carcinoma of oral cavity have a high risk of recurrence after initial treatment with surgery, radiotherapy, surgery with adjuvant radiotherapy, or radio-chemotherapy.The present study investigated the changes in expression, activity and regulation of matrix metalloproteinases (MMP) -2 and -9 in oral squamous cell carcinoma (OSCC) which might help to ascertain the invasive potential of the tumor .Tumor tissues and adjacent normal tissues of OSCC patients [N,37; either sex; 20-70 yrs] were subjected to clinico-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
4
6
0
Order By: Relevance
“…Its main function is to degrade and remodel the ECM, maintain the dynamic balance of ECM, and participate in many pathological and physiological processes in the body. Many of clinical studies have confirmed the high expression of MMP9 and MMP13 in OSCC (Jingqiu et al, 2015; Monteiro et al, 2016; Nanda et al, 2014), which is consistent with our research. Monteiro (Monteiro et al, 2016) applied immunohistochemistry to detect the expression of MMP9 protein in 60 cases of OSCC and found that MMP9 was strongly expressed in cytoplasm of tumor cell in 83.7% of patients, suggesting that MMP9 is a potential tumor marker of oral cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Its main function is to degrade and remodel the ECM, maintain the dynamic balance of ECM, and participate in many pathological and physiological processes in the body. Many of clinical studies have confirmed the high expression of MMP9 and MMP13 in OSCC (Jingqiu et al, 2015; Monteiro et al, 2016; Nanda et al, 2014), which is consistent with our research. Monteiro (Monteiro et al, 2016) applied immunohistochemistry to detect the expression of MMP9 protein in 60 cases of OSCC and found that MMP9 was strongly expressed in cytoplasm of tumor cell in 83.7% of patients, suggesting that MMP9 is a potential tumor marker of oral cancer.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that the TIMP1 gene expression in SAS cells cultured in ALG was significantly lower than that in 2D cells and there was no significant difference in TIMP1 gene expression between ALG and ALG-CS ( Fig. S9a ), which was consistent with the report on TIMP1 in oral squamous cell carcinoma tissues 41 . In addition, we found that higher expression of TIMP1 gene in the 3D-cultured LM3 cells ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidence suggests that MMP9 plays a key positive regulator in OSCC cell migration and invasion across basement membranes 6 . OSCC patients with high MMP9 expression are closely associated with metastatic clinical features and worse prognosis 7 . Although the important biological functions of MMP9 have been clearly elucidated, the mechanism of its dysregulation is still unclear.…”
Section: Introductionmentioning
confidence: 99%